Pengaruh Kepemimpinan Terhadap Motivasi Kerja Pada ULP Woha Kabupaten Bima - Edy Suryadi; Ety Kurniawati (Forum Kerjasama Pendidikan Tinggi, 2020)
In this study leadership is chosen as a variable that affects employee motivation. This study aims to examine and analyze the effect of leadership on the work motivation of Woha Bima Customer Service Unit (ULP) employees. The research method used in this study is a quantitative method with the type of associative explanatory research. The type of data used is primary data with questionnaire data collection methods. The population in this study were all employees of the Bima Regency Woha Customer Service Unit (ULP) totaling 53 people. The sampling technique uses saturated samples by using all existing populations. The analytical tool used is the validity and reliability test of the research instrument. The data analysis is explained explosively which is supported by simple linear regression analysis, correlation coefficient and significant test (t-test). analysis of this data using SPSS 23.0 software. The results obtained in this study are that leadership has a positive and significant influence on the work motivation of Bima Regency Woha Customer Service Units, meaning that if leadership gets better, work motivation increases. This is evidenced by the t-value greater than the t-table value (15.022> 2.007) with a significant level smaller than 0.05 (0.000 <0.05)